2022
DOI: 10.32345/usmyj.2(131).2022.23-31
|View full text |Cite
|
Sign up to set email alerts
|

Ранні Діагностичні Показники Повернення До Тренувально- Змагальної Діяльності У Хокеїстів Після Черепно-Мозкових Травм

Abstract: The aim of study is to develop the criteria for early recovery after sport-related concussions (SRC) with ice-hockey players. 30 professional ice-hockey players from 17 to 30 years (average age 22.7 ± 0.8 from SMS) were included in study. Methods: somatoscopy and somatometry, assessment of autonomic nervous system (ANS), assessment of heart rate variability (HRV), assessment of balance (BESS test). The Buffalo concussion treadmill test (BCTT), which is the most used physicalactivity test after SRC was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…At the preliminary stages of the research, we found a significant impact of autonomic nervous system (ANS) dysregulation on the processes of early recovery in hockey players after CCs [12]. In particular, the necessity of taking into account the tone of the ANS, the level of stress of regulatory systems, and the level of headache when planning rehabilitation and training loads in hockey players after CCs was substantiated [13].…”
Section: Introductionmentioning
confidence: 99%
“…At the preliminary stages of the research, we found a significant impact of autonomic nervous system (ANS) dysregulation on the processes of early recovery in hockey players after CCs [12]. In particular, the necessity of taking into account the tone of the ANS, the level of stress of regulatory systems, and the level of headache when planning rehabilitation and training loads in hockey players after CCs was substantiated [13].…”
Section: Introductionmentioning
confidence: 99%